Mapping cultural diversity: a visualized bibliometric examination of cross-cultural learning - Syed Abdullah, Syed Nurulakla; Haihua, Wang; Abdullah, Muhammad Alif Redzuan (Academic Studies Press, 2024)
The purpose of this endeavor is to identify new areas of interest and research ideas for CCL studies. Design: In this study, the VOS Viewer software is utilized to analyze the gathered data, aiming to discern relationships among nations, institutions, and author keywords by visualizing each main cluster. The study further aims to illustrate the evolution of entrepreneurship and social media research by examining the number of publications, source journals, nations/regions, and keywords across various sub-periods, providing an in-depth analysis of the changing features of international cooperation. Findings: Including "Integrative Medicine Research" (499 citations), which focuses on traditional and alternative medicine with a holistic approach to healthcare. "Economic Geography" (390 citations) explores the spatial organization of economic activities and their impact, examining the relationships between geography, economy, and development. "Computers in Human Behavior" (350 citations) investigates the interaction between humans and technology, delving into the psychological and behavioral aspects of computer usage. "Computers & Education" (329 citations) examines the role of technology in educational settings, emphasizing the impact of computers on learning and teaching. Originality: The discussion section delves into the dynamic patterns in Cross-Cultural Learning publications from 2012 to 2022, exploring fluctuations influenced by factors such as research funding and academic trends. Notably, this study marks a pioneering effort in analyzing bibliographic data specifically about the cultural component within cross-cultural management literature, making a unique contribution to the field.